Prophesying the End of Human Time: Eco-Anxiety and Regress in J. G. Ballard’s Short Fiction - Oramus, Dominika (Text Matters: A Journal of Literature, Theory and Culture, 2022)
Despite being written half a century before the term “eco-anxiety” (Gifford and Gifford) was coined, J. G. Ballard’s disaster fictions can be read in the context of the social psychodynamics of climate change. My aim in this article is to demonstrate that in J. G. Ballard’s fiction, climate catastrophes and the devastation of nature cause the characters to realize that the Earth is not going to be able to sustain human life much longer, and their psychological reaction is either subdued anger or strange numbness. In order to do this, I analyze two short stories by Ballard: “Deep End” (1961) and “Low-Flying Aircraft” (1975) and show how their protagonists are affected by the landscape they inhabit: de-populated wastelands whose wildlife is extinct or mutated. I argue that it is their awareness that human civilization on earth is coming to its end that results in the state of mind akin to eco-anxiety. The characters are immersed in their own inner space and in these stories clocks mark not the passage from past to future but a countdown to the end.